Reanalysis LUSI Stratigraphic Based on Cutting of Banjarpanji#1 Well - Handoko Teguh Wibowo; Bambang Prastistho; C Prasetyadi; Dwi Fitri Yudiantoro (Journal of Earth and Marine Technology (JEMT), 2022)
The subsurface configuration or stratigraphy of the Sidoarjo Hot Mudflow (Lumpur Sidoarjo/LUSI) is used to see what formations are transported out and how the material properties can be known from the well log data of Banjarpanji#1 or BJP#1 well. There is something unusual about the BJP#1 log, namely the presence of solid volcanic sandstone at a depth of 6000-9297 ft where drilling ended. This abnormality was investigated by reanalyzing volcanic sandstone by reading the well log data which is drilling data during the exploration of the Banjarpanji-1 well by PT. Lapindo Brantas, Inc. which consists of rock logs as a result of predictions (prognosis) and facts found (actual) were then compared with the interpretation of the results of the investigation team with BP MIGAS 2006 which was then confirmed by petrographic and paleontological analysis. The unusual occurrence is the LUSI stratigraphic arrangement changes based on findings in volcanic sandstone sequences that were once considered part of the Kalibeng Formation of Plio-Pliestocene age, then changed to solid volcanic sandstone units of Middle Miocene age with a depositional environment in the outer neritic-upper bathyal.